A study on the impact of HIV related stigma on adherence to anti-retroviral treatment among people living with HIV/AIDS in central Kerala, India - Rajmohan, Priyanka; Thomas, Joe; Anthoora Thodi, Jubina Bency; Gopinathan, Unnikrishnan Uttumadathil (International Journal Of Community Medicine And Public Health, 2020)
Background: In India, an estimated 20,88,638 people are living with HIV/AIDS (prevalence 0.27%). The people living with HIV/AIDS (PLHA) are facing double burden of physical and psychosocial impact of infection. This study is conducted to determine prevalence of HIV related stigma among PLHA and to find the association between stigma and adherence to Anti-Retroviral Therapy (ART) among HIV patients in central Kerala. Methods: A cross-sectional study was done from July to December 2018 among 105 adult HIV positive patients who have enrolled in Thrissur Network of People living with HIV/AIDS (TNP PLUS). After obtaining informed consent, the participants were interviewed using a structured interview schedule consisting of questions on socio-demographic details, stigma and ART adherence. Results: The prevalence of high stigma was found to be 21% and moderate stigma 61%.Out of 105 study subjects,68 (64.8%) were found to have a high adherence to ART (≥95%) and 37 (35.2%) were found to have a low adherence (<95%). Patients who had a moderate/high internalized stigma tend to have a low adherence to ART as compared to patients who had low stigma (OR=3.4 (1.2-12.8) p=0.04). On analyzing the association between the different forms of stigma and adherence to ART, isolation by family members, abandoned by friends and verbal stigma were significantly associated with low ART adherence. Conclusions: HIV related internalized stigma was pervasive among the study subjects. These patients also experience other forms of enacted stigma. The presence of internalized stigma was found to be significantly associated with low adherence to ART.